Rhythm perception and music cognition a brief survey - Lima, Leticia Dias de [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2017)
How does our mind process musical rhythm? Based on recent researches and theories on music cognition, the present paper seeks to clarify this question by discussing some issues related to rhythm perception, such as the mental processes involved in the recognition, coding, and retrieval of rhythm and the influence of enculturation and formal musical training on these processes.
Keywords: Rhythm; music perception; music cognition